Measuring Success of PPP Transport Projects: A Cross-Case Analysis of Toll Roads - Liyanage, Champika; Villalba-Romero, Felix (Taylor and Francis Group, 2015)
The aim of this paper is to measure ‘overall’ success of a Public Private Partnership (PPP) transport projects using 04 case studies. All four case studies are PPP toll roads from 04 different EU countries (UK, Spain, Portugal and Greece). The case studies have been analysed using a manual Qualitative Comparative Analysis approach. According to the paper, three different perspectives have been used to measure the success of a project, i.e. project management perspective, stakeholder perspective and contract management perspective. The ‘overall’ success has then been deduced by bringing these three perspectives together as a holistic approach. The findings are presented in a form of a matrix and the final outcome of the paper shows a simple methodological approach that can be used to measure success of a PPP transport project. Since the study takes more of a qualitative approach, researcher bias and perceptions have a major role to play in the final outcome. However, to reduce ‘biasness’, quantitative measures have also been used to quantify the Key Performance Indicators and performance measures in the case studies. It is hoped that the study makes a valid contribution to the areas of transport PPPs and performance measurement.
Keywords: Carreteras - Diseño y construcción; Key performance indicators (KPIs); Performance measures; Project success; PPP (Public Private Partnership); Qualitative Comparative Analysis (QCA); Toll roads